Case Report: A case of infantile acute hyperleukocytic leukemia treated by leukapheresis - Bian, Shuang; Li, Nannan; Gao, Hui (Frontiers in Pediatrics, 2024)
Leukapheresis is a treatment used to reduce leukocytes to decrease the number of white blood cells in circulation and prevent the risks of hyperviscosity, cerebrovascular, and pulmonary leukostasis. We present a case of pro-B cell acute lymphoblastic leukemia with hyperleukocytosis in a six-month-old infant, characterized by a positive KMT2A/AFF1 fusion gene with a leukocyte count of 1755×10 9 /L. After two consecutive sessions of leukapheresis, the white blood cell count decreased to 55×10 9 /L. The infant recovered after the high-dose methotrexate chemotherapy. These results demonstrate that leukapheresis is a feasible treatment option for acute hyperleukocytic leukemia in infants with ALL.